A Survey of the Citizen’s Perception of Government Accountability in the Era of Social Media in Nigeria - Obianefo Chukwujekwu Aloysius; Uchemba Uzochukwu Victor; Okoroji Nma Okechukwu; Okoh Benjamin Chidozie (Jurnal Administrasi Publik (Public Administration Journal), 2022)
The advent of social media in recent times has increased the ways through which the citizenry can hold its government accountable. This study on a survey of the citizen’s perception of government accountability in the era of social media in Nigeria examined two specific objectives which are to ascertain the extent of citizen’s perception of government accountability in the era of social media and to determine the relationship between socioeconomic profile and citizen’s perception of government accountability in social media era in Nigeria. Google form was deployed to various social media platforms for data collection and analysis. The data came in from 150 respondents, downloaded and used. Principal factor analysis and linear regression model were the analytical tools used to achieve the study objectives. The study found that the average age and family sizes were 48 years and 9 people respectively. The average monthly income was 159.09 USD. The extent of citizen’s perception was rotated into three and named as online fear, power of social media, and information availability factors which explained 58.58% total variation in citizen’s perception. The study further found that age, household size, employment status, and monthly income of the respondents were the socioeconomic variables relating to the citizen’s perception in the study area. Seeing that social media is a means to hold the leaders accountable in recent times, the study, therefore, recommends that social media and its platforms should be embraced by our leaders rather than restricting its use in Nigeria.